PERANCANGAN SISTEM INFORMASI MEDIA PROMOSI DIGITAL UNTUK MENDUKUNG PENJUALAN PRODUK PADA ELMO SHOP - Yunus Anis; Sri Mulyani; Sunardi Sunardi (CV. Denasya Smart Publisher, 2026)
Competition in the micro and small business sector demands the use of effective, informative promotional media that can support increased sales. This study aims to design promotional media for Elmo Shop's product sales based on visual communication design as part of a promotional information system to clarify product information delivery and strengthen the business's identity. The method used was descriptive qualitative, with data collection techniques through observation, questionnaires, and literature review. The promotional media design process was conducted using the Luther–Sutopo multimedia development method, which includes the stages of concept, design, material collection, production, testing, and distribution. The research results produced promotional media in the form of business cards, posters, x-banners, and banners that were designed consistently and communicatively. Evaluation using a questionnaire showed that the developed promotional media increased consumer interest and understanding of the product, as well as the effectiveness of Elmo Shop's promotions. Thus, this visual communication design-based promotional media design contributes to supporting the promotional information system and increasing sales potential for micro and small businesses.